SAT0706 End-stage organ failure in sarcoidosis: characterization and predictive factors in 1082 patients. (15th June 2017) - Pérez-Alvarez, R; Kostov, B; González, A García; Torre, R Gόmez De La; Dupla, M Lopez; Escalante, B De; Alguacil, A; Chara, J; Velilla, J; Rascόn, J; Morillo, JS Garcia; Feijoo, C; et al.
Abstract : Objectives: To characterize the main features at presentation of sarcoidosis associated with the development of end-stage organ failure in a large multicenter cohort of patients from Southern Europe. Methods: In January 2017, the Spanish National Registry of Sarcoidosis (SARCOGEAS-SEMI) included 1082 consecutive patients diagnosed with sarcoidosis according to the ATS/ERS/WASOG 1999 statement and extrathoracic involvement to the 2014 WASOG instrument. The development of end-stage organ failure was assessed at the last visit. Results: The cohort consisted of 618 (57%) women and 464 (43%) men, with a mean age at diagnosis of 47yrs. After a mean follow-up of 82 months, 90 (8%) patients developed end-stage organ failure, including respiratory failure (n=56), chronic renal failure (n=13), cardiac failure/permanent cardiac device (n=8) and liver cirrhosis (n=3). The following baseline features were associated with end-stage organ failure in the univariate analysis: patients born in Spain (p=0.008), a higher mean age at diagnosis (p<0.001) and a radiological stage III/IV (p<0.001) With respect to extrathoracic involvement, spleen (p=0.015), renal (p=0.001), cardiac (p=0.028) and bone marrow (p=0.003) involvements, hypercalcemia (p=0.018) and use of corticosteroids (p<0.001) were associated with end-stage organ failure, while patients with cutaneous sarcoidosis had a lower risk (p=0.029). Multivariate analysis identified age at diagnosis (OR 1.05), radiological stages III/IV (OR 3.12) and use of corticosteroids (OR 4.55) as independent variables associated with the development of end-stage organ failure. Conclusions: Nearly 10% of patients with sarcoidosis developed end-stage organ failure. Respiratory failure represented two thirds of cases of sarcoidosis-related organ failure, followed by renal (15% of cases) and cardiac (9%). Older patients, as well as those presenting with advanced radiological stages, had an enhanced risk of developing end-stage organ failure. Disclosure of Interest: None declared